2017
DOI: 10.37236/6730
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Sparse Supersaturation and Extremal Results for Linear Homogeneous Systems

Abstract: We study the thresholds for the property of containing a solution to a linear homogeneous system in random sets. We expand a previous sparse Szémeredi-type result of Schacht to the broadest class of matrices possible. We also provide a shorter proof of a sparse Rado result of Friedgut, Rödl, Ruciński and Schacht based on a hypergraph container approach due to Nenadov and Steger. Lastly we further extend these results to include some solutions with repeated entries using a notion of non-trivial solutions due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…For readers familiar with the notion of partition and density regular (or invariant) matrices, note that they are trivially irredundant and positive. See [12] for an easy proof that they are also abundant. Finally, we introduce a parameter for abundant matrices originally due to Rödl and Ruciński [13].…”
Section: Generalized Van Der Waerden Gamesmentioning
confidence: 99%
“…For readers familiar with the notion of partition and density regular (or invariant) matrices, note that they are trivially irredundant and positive. See [12] for an easy proof that they are also abundant. Finally, we introduce a parameter for abundant matrices originally due to Rödl and Ruciński [13].…”
Section: Generalized Van Der Waerden Gamesmentioning
confidence: 99%
“…Similarly, Schacht showed that for a given density regular matrix AZr×m the threshold probability for the event that [ n ] p is ( δ , A )‐stable is normalΘfalse(n1false/m1false(Afalse)false). The third author as well as independently Hancock, Staden and Treglown extended this result to abundant matrices. Our result shows that the threshold bias of the Maker‐Breaker A ‐game lies around normalΘfalse(n1false/m1false(Afalse)false) for the much broader class of positive and abundant matrices.…”
Section: Discussionmentioning
confidence: 84%
“…For readers familiar with the notion of partition and density regular (or invariant ) matrices in the homogeneous setting, note that they are trivially positive. See for an easy proof that they are also abundant..…”
Section: Introductionmentioning
confidence: 99%
“…Just before submitting the paper we were made aware of simultaneous and independent work of Spiegel [67]. In [67] the case r = 1 of Theorem 4.1 is proven. Spiegel also used the container method to give an alternative proof of Theorem 1.9.…”
Section: Introductionmentioning
confidence: 99%